2017
DOI: 10.1149/2.0421704jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide on Zinc-Modified Copper Electrodes

Abstract: Electrochemical reduction of carbon dioxide (CO 2 ) was performed on zinc-deposited copper (Cu/Zn) electrodes, and the faradaic efficiency of this system toward methane, ethane, and hydrogen was evaluated. Hierarchically structured Zn was electrodeposited on a Cu substrate under constant voltage in a varying bath concentration of Zn to yield low-and high-concentration deposits, represented as Cu/Zn-A and Cu/Zn-B, respectively. The prepared materials were characterized by X-ray diffraction, scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
0
40
2
Order By: Relevance
“…Electroredeposition is another technique to realize the stability of Cu + oxidation state at high negative potential, which is preferable for enhanced catalytic activity of CO 2 ER for the formation of hydrocarbons specifically ethylene . The formation of its bimetallic with other transition metals is a common technique for modification of Cu and its derivatives to prepare new forms of catalyst species such as Sn–Cu, Ni–Cu, Pd–Cu, Au–Cu, etc., which can catalyzes CO 2 better than individual atoms …”
Section: Selected Reduction Products In Co2er On Cu and Its Bimetallicmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroredeposition is another technique to realize the stability of Cu + oxidation state at high negative potential, which is preferable for enhanced catalytic activity of CO 2 ER for the formation of hydrocarbons specifically ethylene . The formation of its bimetallic with other transition metals is a common technique for modification of Cu and its derivatives to prepare new forms of catalyst species such as Sn–Cu, Ni–Cu, Pd–Cu, Au–Cu, etc., which can catalyzes CO 2 better than individual atoms …”
Section: Selected Reduction Products In Co2er On Cu and Its Bimetallicmentioning
confidence: 99%
“…Currently, various efforts are performed to develop and promote green (renewable) energy sources; although until now majority of energy consumption is obtained from nonrenewable sources specifically fossil fuels that contribute the increment of carbon dioxide level in the atmosphere in addition to other causes such as deforestation of plants and natural sources of CO 2. For this reason, controlling and minimization of its emission using different methods such as electrochemical, biochemical, photochemical, thermochemical and hydrothermal reduction of CO 2 to convert into various essential compounds and simultaneously energy generating are one of crucial tasks to solve the challenge …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the selectivity for ethanol (C 2 H 5 OH) versus C 2 H 4 production can be tuned by varying the amount of Zn in the bimetallic catalysts. Keerthiga and Chetty [27] reported that electrodeposition of Zn on a Cu substrate can inhibit HER and enhance CH 4 formation with a faradaic efficiency (FE) of 52 %. Yin et al [28] investigated Cu-Zn alloy materials prepared by a vacuum sealing method for the electrochemical and photoelectrochemical reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…7 While improved selectivity for 2 eproducts has been achieved, success in increasing FE for higher order products has been more limited, as discussed further below. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Comparison among reported Cu-alloy systems is limited by the variation in catalyst syntheses and morphologies in these studies, motivating the systematic study of different alloying elements and alloying concentrations in the present work.…”
mentioning
confidence: 99%